Estimate of severe autosomal recessive limb-girdle muscular dystrophy (LGMD2C, LGMD2D) among sporadic muscular dystrophy males: a study of 415 familes. Issue 12 (December 1995) - Stec, I; Kress, W; Meng, G; Müller, B; Müller, C R; Grimm, T
Abstract : Ninety-five percent of cases of severe muscular dystrophy with early childhood onset result from mutations in the dystrophin region of the human X chromosome (DMD, McKusick 310200), whereas 5% are thought to result from mutations in autosomal genes. We examined a total of 415 families with at least one living patient whose clinical features suggested DMD. Based on formal genetics, haplotype analysis, and dystrophin determinations, we estimate that one in eight (11.8%) sporadic male patients carries autosomal rather than X chromosomal mutations.